IMPACT OF MOVIE-BASED SIMULATION TRAINING, WITH OR WITHOUT CONVENTIONAL VERBAL DEMONSTRATION ON OBSERVED OSPE SCORES IN MEDICAL UNDERGRADUATES: A DOUBLE CONTROL STUDY - Malik, Samina; Zaheer, Reema; Bilal, Muhammad (Journal of Ayub Medical College Abbottabad, 2013)
Background: Movie-based simulation training may be useful in delivering the preclinical observed OSPE curriculum, minimising the need of subjects/patients; however, a double-control trial needs to be performed and optimal timing and duration of training is yet to be defined. Likewise, gender-based response and students' feedback has to be assessed. The objective of this study was to compare the movie-based and traditional verbal demonstration teaching methodologies. Methods: Second-year medical undergraduates (n=90) of Avicenna Medical College were randomised to movie-based simulation training (group B, n=30), traditional verbal training alone (group C, n=30), and a combination (group A, n=30). The scores were marked by observers using a standardised key and were compared for performance at 2 observed OSPE stations. Results: Group B and A performed significantly better than group C on station 1 and 2. Gender factor did not seem to influence the score. A total of 99% students reported that combination of the 2 teaching modes is the best option. They believed it offers more clear understanding with interest (61%), long term memory (21%), use of both senses; seeing & hearing (10%) & better focus of attention (3%). Conclusion: Even half an hour of movie-based simulation training with traditional instructor-based training may improve student performance significantly, and the students prefer a combination of the both. Keywords: Movie-based simulation training, Conventional verbal demonstration, OSPE, Medical education, visual-learning